Workplace risk factors for cancer in the German rubber industry: Part 1. Mortality from respiratory cancers. Issue 5 (May 1998) - Weiland, S K; Straif, K; Chambless, L; Werner, B; Mundt, K A; Bucher, A; Birk, T; Keil, U
Abstract : OBJECTIVES: To determine the cancer specific mortality by work area among active and retired male workers in the German rubber industry. METHODS: A cohort of 11, 663 male German workers was followed up for mortality from 1 January 1981 to 31 December 1991. Cohort members were classified as active (n = 7536) or retired (n = 4127) as of 1 January 1981 and had been employed for at least one year in one of five study plants producing tyres or technical rubber goods. Work histories were reconstructed with routinely documented "cost centre codes" which were classified into six categories: I preparation of materials; II production of technical rubber goods; III production of tyres; IV storage and dispatch; V maintenance; and VI others. Standardised mortality ratios (SMRs) adjusted for age and calendar year and 95% confidence intervals (95% CIs), stratified by work area (employment in respective work area for at least one year) and time related variables (year of hire, lagged years of employment in work area), were calculated from national reference rates. RESULTS: SMRs for laryngeal cancer were highest in work area I (SMR 253; 95% CI 93 to 551) and were significant among workers who were employed for > 10 years in this work area (SMR 330; 95% CI 107 to 779). Increased mortality rates from lung cancer were identified in work areas I (SMR 162; 95% CI 129 to 202), II (SMR 134; 95% CI 109 to 163), and V (SMR 131; 95% CI 102 to 167). Mortality from pleural cancer was increased in all six work areas, and significant excesses were found in work areas I (SMR 448; 95% CI 122 to 1146), II (SMR 505; 95% CI 202 to 1040), and V (SMR 554; 95% CI 179 to 1290). CONCLUSION: A causal relation between the excess of pleural cancer and exposure to asbestos among rubber workers is plausible and likely. In this study, the pattern of excess of lung cancer parallels the pattern of excess of pleural cancer. This points to asbestos as one risk factor for the excess deaths from lung cancer among rubber workers. The study provides further evidence for an increased mortality from laryngeal cancer among workers in the rubber industry, particularly in work area I.